Dukungan Keluarga dalam Merawat Anak dengan Talasemia: a Narrative Review - Nabilah, Nurul Azmi; Komariah, Maria; Mediani, Henny Suzana (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Thalassemia is a significant global health problem, with many challenges in the treatment process. Parents, especially mothers, generally act as the main care givers for their children's care, so it is not only the child who feels the impact of the disease, but also the parents. To explore the support that mothers need in accompanying their child's care process. This study used a narrative review design that followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) procedures for article selection. Inclusion criteria included articles that addressed maternal support for child care, were published within the last five years, and were in English. Data were analyzed by identifying key themes related to maternal support. The results of the article analysis showed that there were 6 articles that discussed maternal support in assisting child care. The support obtained included informational, emotional, spiritual, financial, social, and professional support. The need for a holistic approach to improve the role of nurses in intervening in the form of collaborative interventions with other health workers. Keywords: Children, Family, Support, Thalassemia  ABSTRAK Talasemia merupakan masalah kesehatan global yang signifikan, dengan banyak tantangan proses perawatannya. Orang tua, khususnya ibu umumnya berperan sebagai care giver utama bagi perawatan anak sehingga bukan hanya anak yang merasakan dampak dari penyakit, orang tua pun ikut mengalami dampak dari penyakit yang diderita oleh anak. Untuk mengeksplorasi dukungan yang dibutuhkan keluarga dalam mendampingi proses perawatan anak. Penelitian ini menggunakan desain narrative review yang mengikuti prosedur PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) untuk seleksi artikel. Kriteria inklusi mencakup artikel yang membahas dukungan keluarga dalam mendampingi perawatan anak, dipublikasikan dalam lima tahun terakhir, dan menggunakan bahasa inggris. Analisis data dilakukan dengan mengidentifikasi tema-tema utama terkait dukungan keluarga. Hasil dari analisis artikel menunjukkan terdapat 6 artikel yang membahas tentang dukungan keluarga dalam mendampingi perawatan anak. Dukungan yang diperoleh diantaranya dukungan informasi, emosional, spiritual, finansial, sosial, dan profesional. Perlunya pendekatan holistik untuk meningkatkan peran perawat dalam melakukan intervensi berupa intervensi kolaboratif dengan tenaga kesehatan lainnya. Kata Kunci: Anak, Dukungan, Keluarga, Talasemia